A new player in the game: treatment with antagomiR-21a-5p significantly attenuates histological and echocardiographic effects of experimental autoimmune myocarditis. Issue 2 (23rd January 2021) - Mirna, Moritz; Paar, Vera; Topf, Albert; Kraus, Theo; Sotlar, Karl; Aigner, Achim; Ewe, Alexander; Watzinger, Simon; Podesser, Bruno K; Hackl, Matthias; Pistulli, Rudin; Hoppe, Uta C; et al.
Abstract: Aims : Myocarditis is associated with formidable symptoms and increased risk of adverse outcomes. Current approaches mostly rely on symptomatic treatments, warranting novel concepts for clinical practice. The aim of this study was to investigate the microRNA (miRNA) expression profile of Balb/c mice with experimental autoimmune myocarditis (EAM), choose a representative miRNA to antagonize after review of available literature and test its effects on myocardial inflammation in vitro and in vivo . Methods and results : Phase 1: EAM was induced in 12 male Balb/c mice, 10 animals served as controls. After sacrifice, next-generation sequencing (NGS) of the miRNA expression profile was performed. Based on these results, H9C2 cells and human ventricular cardiac fibroblasts exposed to lipopolysaccharide (LPS) were treated with the selected candidate antagomiR-21a-5p. Phase 2: EAM was induced in 48 animals. Thereof, 24 animals were either treated with antagomiR-21a-5p or negative control oligonucleotide in a nanoparticle formulation. Transthoracic echocardiography (TTE) was performed on Days 0, 7, 14, and 21. Histopathological examination was performed after sacrifice. Phase 1: EAM resulted in a significant up-regulation of 27 miRNAs, including miR-21a-5p (log2FC: 2.23, adj. P = 0.0026). Transfection with antagomiR-21a-5p resulted in a significant reduction of TNFα, IL-6, and collagen I in vitro . Phase 2: Treatment with antagomiR-21a-5p, formulated in polymeric nanoparticles for systemic injection, significantly attenuated myocardial inflammation ( P = 0.001) and fibrosis ( P = 0.013), as well as myocardial 'hypertrophy' on TTE. Conclusions : Silencing of miR-21a-5p results in a significant reduction of the expression of pro-inflammatory cytokines in vitro, as well as a significant attenuation of inflammation, fibrosis and echocardiographic effects of EAM in vivo . Graphical Abstract: